ELEMENTOS DE ANÁLISIS SOBRE LA REPRODUCCIÓN CAMPESINA - Chacón, Isidora (1994)
Agricultural sector, particularly peasant, keep on occupying a very important place in our country. Peasantry concept and elements present in its permanent persistence and differenciation, which deserves a continuos study and conceptual revision as well as revision of the reality the express.